2013
DOI: 10.1128/aem.03905-12
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitrogen Limitation in Transformation of RDX (Hexahydro-1,3,5-Trinitro-1,3,5-Triazine) by Gordonia sp. Strain KTR9

Abstract: bThe transcriptome of RDX (hexahydro-1,3,5-trinitro-1,3,5-triazine)-degrading strain Gordonia sp. strain KTR9 and its glnR mutant were studied as a function of nitrogen availability to further investigate the observed ammonium-mediated inhibition of RDX degradation. The results indicate that nitrogen availability is a major determinant of RDX degradation and xplA gene expression in KTR9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…KTR9. In agreement with our findings, studies of an xplR knockout demonstrated that XplR is not involved in RDX degradation (29). Studies of the xplAB-containing gene cluster in Gordonia sp.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…KTR9. In agreement with our findings, studies of an xplR knockout demonstrated that XplR is not involved in RDX degradation (29). Studies of the xplAB-containing gene cluster in Gordonia sp.…”
Section: Discussionsupporting
confidence: 80%
“…In agreement with our findings, previous studies using Gordonia sp. KTR9 and a global nitrogen regulation (glnR) mutant of KTR9 indicated that nitrogen availability plays a role in the regulation of xplA (29). Beyond this conclusion, our studies also show that RDX removal was further increased in cells grown in RDX prior to resting-cell assays, and under these conditions, XplA protein and activity levels increased correspondingly.…”
Section: Discussionsupporting
confidence: 61%
“…4a). In all four cases, the ammonium concentration decreased to undetectable levels after 6 h. Previously, growing cultures of wild-type KTR9 and the glnR mutant with excess nitrogen exhibited a similar pattern of ammonium utilization (Indest et al 2013). Thus, RDX does not inhibit assimilation of ammonium by either strain.…”
Section: N Assimilation In Cell Suspensionsmentioning
confidence: 86%
“…A previous study (Indest et al 2013) concluded that the putative regulatory protein XplR, encoded by a gene located upstream of the xplAB gene cluster in KTR9, does not appear to regulate RDX degradation. The current study found that the global regulator of N assimilation, GlnR, is essential for KTR9 to degrade RDX and use it as an N source, but GlnR is not essential for xplA transcription.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation